A Bayesian network meta-analysis: Comparing the clinical effectiveness of local corticosteroid injections using different treatment strategies for carpal tunnel syndrome. Issue 1 (December 2015) - Chen, Po-Cheng; Chuang, Ching-Hui; Tu, Yu-Kang; Bai, Chyi-Huey; Chen, Chieh-Feng; Liaw, Mei-
Abstract Background Local corticosteroid injections are commonly used to improve the short-term symptomatic severity and the functional status of the hands affected by carpal tunnel syndrome. We conducted a systematic review and Bayesian network-meta-analysis to compare the clinical effectiveness of local corticosteroid injections using different injection approaches. Methods Electronic literature in Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, Web of Science, and other sources were searched to identify clinical studies comparing different injection approaches with each other or placebo for carpal tunnel syndrome. Two review authors conducted selection of studies, data extraction, and assessment of risk of bias independently. Random-effects models were used to conduct the pairwise meta-analysis and the Bayesian network meta-analysis. Results Overall, 10 studies with 633 patients were included in the systematic review. Among the injection approaches, local corticosteroid injections using the ultrasound-guided in-plane injection (Ulnar-I) approach was the best treatment strategy for clinical response (median OR versus placebo 128.30, 95 % CrI 9.76 to 2299.00), change in symptom severity scale (median MD versus placebo −1.16, 95 % CrI −1.95 to −0.38), and change in functional status scale (median MD versus placebo −0.74, 95 % CrI −2.00 to 0.52) at short-term follow-up period in the network meta-analysis. Local corticosteroid injections using other injection approaches were better than placebo for clinical response (for the PI approach, median OR versus placebo 8.85, 95 % CrI 3.00 to 33.15; for the DI approach, median OR versus placebo 7.00, 95 % CrI 0.53 to 118.80), change in symptom severity scale (for the Ulnar-O approach, median MD versus placebo −0.78, 95 % CrI −1.43 to −0.16; for the PI approach, median MD versus placebo −0.58, 95 % CrI −0.95 to −0.22), and change in functional status scale (for the Ulnar-O approach, median MD versus placebo −0.63, 95 % CrI −1.67 to 0.43; for the PI approach, median MD versus placebo −0.46, 95 % CrI −1.11 to 0.21) at short-term follow-up period. The quality of studies is good. Conclusions According to our analyses, the ultrasound-guided in-plane injection (Ulnar-I) approach was the most effective treatment among the injection approaches for carpal tunnel syndrome.